Obinutuzumab combined with bendamustine for the treatment of hairy cell leukemia variant: a case report and literature review - Bai, Junjun; Zhang, Yi; Lv, Kangqi; Zhang, Bei; Wang, Hongxia; Pei, Zhixin; Zhao, Yingxin; Gu, Jingjing; Wu, Huimin; Song, Qinglin (Frontiers in Oncology, 2025)
Hairy cell leukemia variant (HCL-v) is a rare and more aggressive subtype of B-cell leukemia. While it shares certain clinical features with classical hairy cell leukemia (HCL-c), HCL-v typically follows a more malignant course and responds poorly to conventional therapies. We report a case of HCL-v in a 57-year-old male who was admitted with splenomegaly and abnormal blood counts. Based on bone marrow morphology and immunophenotyping, a diagnosis of HCL-v was established. The patient was treated with a combination of obinutuzumab and bendamustine. Following treatment, his blood counts normalized, spleen size significantly reduced, and bone marrow reassessment confirmed complete remission (CR) with minimal residual disease (MRD) negativity. The patient is currently undergoing maintenance therapy with obinutuzumab and remains in good clinical condition. This case demonstrates the promising clinical efficacy of obinutuzumab combined with bendamustine in treating HCL-v, suggesting its potential as a therapeutic option. However, long-term outcomes warrant further investigation.